Hubungan Antara Indeks Massa Tubuh dan Nilai Kapasitas Vital Paksa Paru Pada Pasien Penyakit Paru Obstruktif Kronis Stabil Derajat 2 di Balai Besar Kesehatan Paru Masyarakat Surakarta - Yuwono, Karsa Lugi (2016)
ABSTRACT The Correlation between Body Mass Index and the value of Lung Forced Vital Capacity in stable patients of Chronic Obstructive Pulmonary Disease Stage II at Balai Besar Kesehatan Paru Masyarakat Surakarta Karsa Lugi Yuwono1, Niwan Tristanto Martika2, Sri Wahyu Basuki2 Background: The decreasing in Forced Vital Capacity of the lung is in line with the increasing duration of exposure and the concentration of pollutants. Patients with COPD often experience weight loss and based on population studies and indicators used in determining the nutritional status, 19-60% of patients are malnourished. Nutrients that are less related to the severity of obstructive airways and low FEV1 and FVC are directly correlated with high mortality and morbidity. Body mass index (BMI) is a simple way to monitor the nutritional status of adults Method: This study uses observational analytic study with a cross-sectional design. The study was conducted in November 2015 took place at Balai Besar Kesehatan Paru Masyarakat Surakarta with sample of men and women aged> 40 years. The minimum sample sized by 17 subjects. The method of sampling uesd is purposive sampling techniques Data were analyzed using SPSS 22.0 Result: Value of Pearson correlation = 0.501 and P = 0.002. This is indicates that there is a positive correlation between BMI and FVC in patients with stable COPD stage II with the strength of the correlation is strong enough. Conclusion: Body mass index was positively correlated with the value of the Forced Vital Capacity of the lung in patients with stable COPD stage II. Keywords: Body Mass Index (BMI), Forced Vital Capacity (FVC) 1Student of Faculty of Medicine of Universitas Muhammadiyah Surakarta 2Lecturer of Faculty of Medicine of Universitas Muhammadiyah Surakarta